(untitled) (ҚазҰУ хабаршысы. Экология сериясы, 2016)
This article contains the tables which offer a structure of the family of taxonomic Labiatae of Central Kazakhstan. At the present stage the family is represented by 50 species belonging to 20 types, which compose 22 % of the total number of species ofKazakhstan’s flora and 42.6 % of total births. The two types take a central place in species diversity: Thymus L. и Scutellaria L. The sort of Thymus L. Represented by 12 species in Central Kazakhstan: T. asiaticus Serg., T. crebrifolius Klok., T. eremita Klok., T. guberlinensis Iljin, T. kasakstanicus Klok., T. kirgisorum Dub., T. lavrenkoanus Klok., T. marschallianus Willd., T. minussinensis Serg., T. rasitatus Klok., T. roseus Schipz., T. stepposus Klok.et Schost. A distribution of Labiatae flora species is offered as a chart.10 leading families of the flora of Central Kazakhstan is described in the table 2: Asteraceae, Fabaceae, Cruciferae, Cereals, Chenopodiaceae, Caryophyllaceae, Labiatae, Boraginaceae, Umbrella, Fig-wort. The authors of this article carry out a research some of the spreading plants of Labiatae family in Central Kazakhstan and 7 maps of the regions are also worked out by them. At the end of the article there is a conclusion and references which were used in writing this article.